Geochemical and microtextural characteristics reflect the formation mechanics of laminated iron deposits at the Perle & Bruse and Troll Wall vent fields - Lyngtveit, Tarje Javnes (The University of Bergen, 2017)
Located at the southern section of the Artic Mid-Ocean Ridge, the Jan Mayen Vent Fields (JMVF) consist of three main hydrothermal sites, the Troll Wall, Perle & Bruse and Soria Moria. These sites contain numerous Fe-deposits, located distal to high-temperature venting sites. A recent study of such Fe-deposits from the Troll Wall reports of abundant neutrophilic Fe-oxidizing bacteria (FeOB), at locations with active low-temperature venting. The same study suggests that the stratified structure, and textural and chemical variations of the laminae and layers of the deposits reflect changes in physicochemical conditions (i.e. temperature, fluid dynamics, pH, nutrient availability), which govern the formation processes, such as habitability and growth of biomineralizing FeOB, and abiotic mineralization. In this study samples of Fe-depositsfrom both the Troll Wall and Perle & Bruse vent fields are characterized by scanning electron microscopy (SEM) and geochemical analysis, with the aim of establishing possible intra- and inter-field textural and geochemical variations at these sites, and if such variations can be explained by similar physicochemical changes. The textural results reveal that the samples from both fields are built up of stacked sequences of five distinct laminae or laminated layers of different colour, thickness, porosity and microtextures, separated by internal cavities. A yellow and a light brown layer with a highly porous framework of 10-50 μm thick, 200μm to >1000μm long bundles of 0.3-1μm wide fibres, which apparently grew inward from an outer glass-like lamina and into the cavities, form the innermost layers in each sequence. The fibres were likely formed through nucleation onto extracellular polymers (EPS). Secondary mineral coating and attached twisted FeOB stalks on the bundles in the light brown layer suggest a further development from the yellow stage through different biotically and abiotically dominated stages. Clusters of 2-3 μm wide, branching tubes (Y-guys) associated with ...